Identification of ς(B)-Dependent Genes in Bacillus subtilis Using a Promoter Consensus-Directed Search and Oligonucleotide Hybridization - Petersohn, Anja (American Society for Microbiology, 1999)
A consensus-directed search for ς(B) promoters was used to locate potential candidates for new ς(B)-dependent genes in Bacillus subtilis. Screening of those candidates by oligonucleotide hybridizations with total RNA from exponentially growing or ethanol-stressed cells of the wild type as well as a sigB mutant revealed 22 genes that required ς(B) for induction by ethanol. Although almost 50% of the proteins encoded by the newly discovered ς(B)-dependent stress genes seem to be membrane localized, biochemical functions have so far not been defined for any of the gene products. Allocation of the genes to the ς(B)-dependent stress regulon may indicate a potential function in the establishment of a multiple stress resistance. AldY and YhdF show similarities to NAD(P)-dependent dehydrogenases and YdbP to thioredoxins, supporting our suggestion that ς(B)-dependent proteins may be involved in the maintenance of the intracellular redox balance after stress.